Post-mortem brain histological examination in the substantia nigra and subthalamic nucleus in Parkinson’s disease following deep brain stimulation - Mazumder, Srestha; Bahar, Anita Y.; Shepherd, Claire E.; Prasad, Asheeta A. (Frontiers in Neuroscience, 2022)
Parkinson’s disease (PD) is a progressive neurodegenerative disorder; pathologically hallmarked by the loss of dopamine neurons in the substantia nigra (SN) and alpha-synuclein aggregation. Deep brain stimulation (DBS) of the subthalamic nucleus (STN) is a common target to treat the motor symptoms in PD. However, we have little understanding of the cellular changes in the STN during PD and the impact of DBS on the STN and SN is limited. We examined cellular changes in the SN and STN in PD patients with and without STN-DBS treatment. Post-mortem brain tissue from 6 PD non STN-DBS patients, 5 PD STN-DBS and 6 age-matched controls were stained with markers for neurodegeneration (tyrosine hydroxylase, alpha-synuclein and neuronal loss) and astrogliosis (glial fibrillary acidic protein). Changes were assessed using quantitative and semi-quantitative microscopy techniques. As expected, significant neuronal cell loss, alpha-synuclein pathology and variable astrogliosis was observed in the SN in PD. No neuronal cell loss or astrogliosis was observed in the STN, although alpha-synuclein deposition was present in the STN in all PD cases. DBS did not alter neuronal loss, astrogliosis or alpha synuclein pathology in either the SN or STN. Conclusion: This study reports selective pathology in the STN with deposits of alpha-synuclein in the absence of significant neuronal cell loss or inflammation in PD. Despite being effective for the treatment of PD, this small post-mortem study suggests that DBS of the STN does not appear to modulate histological changes in astrogliosis or neuronal survival; suggesting that the therapeutic effects of DBS mechanism may transiently affect STN neural activity.